Regulation of Mitochondrial Dynamics by Aerobic Exercise in Cardiovascular Diseases - Gu, Changping; Yan, Jie; Zhao, Liang; Wu, Guanghan; Wang, Yue-lan (Frontiers in Cardiovascular Medicine, 2022)
Mitochondrial dynamics plays an important role in improving cardiovascular homeostasis. This process refers to the continuous biogenesis, fusion, fission and degradation of mitochondria to maintain the integrity, distribution, size and function of mitochondria. Aerobic exercise is a recognized non-drug intervention that improves cardiovascular health in healthy and ill individuals and reduces overall mortality of cardiovascular diseases. There is increasing evidence that aerobic exercise can effectively regulate the coordinated circulation of mitochondrial dynamics, thus inhibiting the development of cardiovascular disease. This review will summarize the role of mitochondrial dynamics in the benefits and risks of aerobic exercise for cardiovascular function.